1987
DOI: 10.1111/j.1365-2621.1987.tb06664.x
|View full text |Cite
|
Sign up to set email alerts
|

National Consumer Retail Beef Study: Palatability Evaluations of Beef Loin Steaks that Differed in Marbling

Abstract: Top loin steaks from strip loins selected from 700 beef carcasses representing seven degrees of marbling (Slightly Abundant through Traces) were randomly assigned to untrained consumers (n = 180 per city) in San Francisco, Philadelphia and Kansas City. Statistical analyses revealed a significant marbling level x city interaction. As marbling level decreased from Slightly Abundant to Traces, consumers in San Francisco and Kansas City gave consistently high ratings that were only slightly reduced as marbling was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
3
6

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(128 citation statements)
references
References 2 publications
4
115
3
6
Order By: Relevance
“…(3) The household panel in Houston, TX, which ranked loin steaks as low prime = high choice = average choice > low choice = upper half select = lower half select = upper half standard > bullocks full width of select = steers full width of select (P < 0.05). Savell et al (1987) reported that:…”
Section: Palatability Prediction Using Usda Quality Gradesmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) The household panel in Houston, TX, which ranked loin steaks as low prime = high choice = average choice > low choice = upper half select = lower half select = upper half standard > bullocks full width of select = steers full width of select (P < 0.05). Savell et al (1987) reported that:…”
Section: Palatability Prediction Using Usda Quality Gradesmentioning
confidence: 99%
“…Smith (2005) composited data from the studies of Smith et al (1980Smith et al ( , 1983Smith et al ( , 1984Smith et al ( , 1987, Branson et al (1984Branson et al ( , 1986, Savell et al (1987), Jones and Tatum (1991a, 1991b, Huffhines et al (1992aHuffhines et al ( , 1992bHuffhines et al ( , 1993 and George et al (1999) and concluded that the odds of having an unpleasant eating experience are 1 in 33 (3%) if a middle-meat steak comes from a prime carcass, as compared with 1 in 10 (10%), 1 in 6 (16%), 1 in 4 (27%) or 1 in 2 (50%) if a middle-meat steak comes from a carcass of upper two-thirds choice, lower one-third choice, select or standard grades, respectively. Platter et al (2003b) reported that: (i) marbling score displayed a significant relationship to acceptance of steaks by consumers; and (ii) the shape of the predicted probability curve for steak acceptance was approximately linear over the entire range of marbling scores (TR 67 to SA 97 ), suggesting that the likelihood of consumer acceptance of steaks increases~10% for each full marbling score increase between SL and SA.…”
Section: Palatability Prediction Using Usda Quality Gradesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Aberle et al (1981) indicated that feeding a high-energy diet for a shor-t period ( -70 d) All unstimulated sides were broken into primal cuts that were then separated into fat, lean and bone according to the procedure described by Rahnef'eld et al (1983) to improved consumer ratings (Savell et al 1987). However.…”
mentioning
confidence: 99%
“…Despite previous results showing differences in flavor liking between TC and SE top loins steaks (Corbin et al, 2015;Hunt et al, 2014;Tedford et al, 2014), TC and Select were rated similarly (P > 0.05) for flavor liking in our current study. However, differences in beef production systems, such as those in the U.S. compared to those in Central America, can affect flavor (Smith et al, 1985;Savell et al, 1987). Beef from animals raised on a finishing diet with grains tend to deposit more fat (Duckett et al, 2007;Duckett et al, 2013), positively affecting flavor (Umberger et al, 2000).…”
Section: Consumer Flavor Likingmentioning
confidence: 99%